RODOFEBISU – Trading Support System - Tkachenko, Olexandr; Kutsenko, Mykyta; Fleshner, Hlib (Cifrova platforma: ìnformacìjnì tehnologìï v socìokulʹturnìj sferì, 2022)
The purpose of the article is to study, analyze and consider the general problems and prospects of developing software for trading RodOfEbisu with the possibility of automated trading based on a recommendation algorithm. The research methods are the basic methodologies and algorithms for successful trading. The article considers approaches to the development and operation of software for automated trading. The novelty of the research is the analysis of modern trading methods in different markets, the results of which can be used in the development of its own trading automation product, which is an assistant and, possibly, can become an independent unit. Conclusions. The paper investigates the existing views on the modern approach to decision-making and buying, which can be used to develop its own product – a trader’s assistant. Taking into account the results of the analysis, it was decided to develop software for trading RodOfEbisu, which can act as an advisor and executor, with the possibility of using different trading strategies.